The Effect of Stabilization Spent Bleaching Earth using Seashell Towards Compressive Strength and Water Blasting Damages of Concrete - Muhammad Gala Garcya; Faisal Ananda; Juli Ardita Pribadi R; Zulkarnain; Alamsyah; Armada (Journal of Infrastructure and Civil Engineering, 2026)
Palm Crude Oil (CPO) production generates substantial waste, including Spent Bleaching Earth (SBE), which is difficult to recycle. This research explores the stabilization of SBE using seashells for use in concrete mixtures. The goal is to enhance concrete’s durability by utilizing the calcium content in stabilized SBE. In this study, we tested concrete with a design strength of 30 MPa. The tests included compressive strength on 150x300 mm cylinders, flexural strength on 600x150x150 mm beams after 28 days of curing, and water blasting resistance using two methods. The water blasting test assessed the concrete’s resistance to water pressure on 500 x 350 x 50 mm samples over three consecutive days. The results showed that concrete with a 7.5% SBE variation achieved a compressive strength of 42.06 MPa, higher than the design strength. Flexural strength increased by 4.67% with a 10% variation in SBE. However, the water blasting tests revealed that both concrete variations exhibited greater damage than normal concrete, indicating that while SBE improves compressive and flexural strength, it may reduce the concrete’s water resistance.